Examining the effects of short-term energy restriction on liver lipid, metabolism and inflammatory status in severely obese adults - Baldry, Emma (2017)
A pre-operative energy restrictive diet is common practice prior to bariatric surgery in the United Kingdom. A review of current practice found variability in form, duration and application of the diet used, with little evidence for efficacy beyond patients successfully undergoing surgery. Imperative for best practice was to provide evidence of the efficacy of dietary approaches both in terms of the original aim of the diet to reduce liver size and improve access to enable laparoscopic surgery, but also to investigate the wider effects of the diet on this population.